Citizen Participation in Public Adminitration: A Review Literature - Salampessy, Maryam; Nungraha, Aat Ruchiat; Sjoraida, Diah Fatma; Wijoyo, Hadion; Rasyid, Rasyid; Santosa, Tomi Apra; Kurniawan, Andri; Wulandari, Andi Sri Rezky (eScience Humanity Journal, 2024)
This study aims to comprehensively review the literature related to citizen participation in public administration. Citizen participation is an important element in increasing transparency, accountability, and governance effectiveness. This study uses a literature review method to analyze the concepts, dimensions, supporting factors, and challenges that affect citizens' involvement in public administration. The results of the study show that citizen participation can be implemented through various forms, such as consultation, dialogue, collaboration, and direct empowerment. Digital technologies, such as e-governance and social media, have expanded the space for participation, although there are still obstacles such as inequality in access to technology, lack of digital literacy, and bureaucratic resistance. Other factors that play a role include inclusive policies, responsive leadership, and a participatory culture in society. In addition, citizen participation not only improves the quality of public services, but also strengthens democracy. The study provides recommendations for developing a strategic framework to integrate citizen participation into public administration more effectively, with a focus on sustainability, inclusivity, and adaptation to technological change.